Nursing Practice Combined with Scene Simulation Teaching Mode in Standardized Training and Teaching for Newly Recruited Nurses in Post Anesthesia Care Unit - Lijuan Guo; Xiaorong Yin; Xiaoqi Zeng; Lu Tang; Dengsuo Zhang (Tehran University of Medical Sciences, 2022)
Background: To explore the application of nursing practice combined with scene simulation teaching mode in standardized training and teaching for newly recruited nurses in Post Anesthesia Care Unit (PACU) and its impact on their emergency response ability and competence. Methods: From Jan 2019 to Jan 2020, a total of 120 PACU nurses with professional qualification certificates in West China Hospital Sichuan University, Chengdu, China were enrolled and randomized into group A (n=60) and group B (n=60). Conventional standardized PACU training and teaching was applied in group B, and nursing practice combined with scene simulation teaching mode was applied in group A. After training for 12 weeks, the examination scores, competence and emergency response ability in the two groups were compared. Results: After training, the scores of theoretical examination, comprehensive scene simulation and nursing document in group A were conspicuously higher than those in group B (P<0.001). After training, the competence and emergency response ability in group A were significantly higher than those in group B (P<0.001). Conclusion: With a better training effect, nursing practice combined with scene simulation teaching mode can enhance the emergency response ability and competence for nurses in PACU, which should be promoted in practice.